Michael Dante DiMartino's Hero's Journey of Avatar Korra: The Legend of Korra - Muhamad Akbar Wardhany (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study aims to analyze Korra's Hero's Journey in the series Avatar: The Legend of Korra and the character changes she undergoes through a series of events, using the Hero's Journey theory and a psychoanalytic approach. Specifically, this study delves into how Korra's internal emotional development mirrors the transformation within the Initiation stage. Data was collected from various sources such as books, journals, series dialogues, and websites. The findings indicate that Korra's internal emotional development during the Initiation stage indeed illustrates significant transformational aspects for her journey. This research is expected to provide further insight into the analysis of this series using the Hero's Journey approach.